GROWTH, YIELD AND QUALITY OF GUAVA (PISIDIUM GUAJAVA L.) AS INFLUENCED BY DIFFERENT LEVELS OF NUTRIENTS UNDER RAINFED REGION OF RAINFED REGION OF RAINFED REGION OF KYMORE PLATEAU - SINGH, T. K.; MAHAJAN, GAURAV; KUMAR, ASHISH; KUMAR, PRASHANT (The Bioscan, 2015)
Under rainfed region of Kymore plateau in M.P., It was found that fruit yield of guava was increased by 15.64% with the application of 75g N/plant to 25.72% at 150g N/plant as compared to no nitrogen application. The application of phosphorus at the rate of 150g P2O5 per plant gave 6.51% higher number of fruit, 2.77% higher fruit weight and 38.63% higher fruit yield/plant as compared to no phosphorus application. The yield of guava due to application of 150g K2 O/plant was not affected significantly but gave 2.44% higher fruit yield as compared to no potash application. The increased dose of nitrogen and phosphorus was significantly correlated with different growth and yield characters of guava for yield maximization NPK requirement were 154.12 g N/plant, 170.75 g P2 O5 /plant and 184.37 g K2O/plant. Maximum values of 12.03º, 12.23º and 12.00 ºBrix was observed with highest dose of nutrient application.